The Role of Entrepreneurship in Enhancing the Creativity of SMK Muhammadiyah Watansoppeng Students in the Digital Era - Mutmainnah Mutmainnah; Erlangga Erlangga; Nurul Ashira; Mariana Mariana; Nurmayanti Nurmayanti; Sam Hermansyah (Edumaspul: Jurnal Pendidikan, 2024)
The increasing pace of globalization presents various challenges that affect multiple aspects of human life, including the economy. This phenomenon necessitates immediate change and innovation. One effective approach to addressing these issues is equipping the younger generation with entrepreneurial skills, preparing them to compete in an increasingly competitive market and creating new opportunities that can enhance national competitiveness. This study explores how entrepreneurship contributes to fostering creativity among students at SMK Muhammadiyah Watansoppeng. By integrating entrepreneurial concepts into classroom learning, students gain the opportunity to develop creative ideas, solve problems, and enhance their creative thinking skills. The research demonstrates that when entrepreneurship is applied in education, students not only learn to be innovative and entrepreneurial but also build the necessary competencies to succeed in the modern workforce. Keywords: Entrepreneurship, Creativity, SMK Muhammadiyah Watansoppeng.